Gender Differences in Early Childhood Vocabulary Acquisition: A Systematic Literature Review of Cognitive, Social, and Environmental Influence - Fahriany Fahriany (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This literature review examines gender differences in early childhood language acquisition through interactions among biological, cognitive, and sociocultural factors. Using a systematic review of research from the past two decades (14 primary studies and additional sources), the study finds that girls generally outperform boys in vocabulary, grammar, and communicative competence—achieving language milestones earlier, showing greater verbal fluency, and exhibiting more advanced pragmatic skills. These differences relate to cognitive advantages such as stronger verbal memory, faster language processing, and better executive functioning. Sociocultural factors—parental language input, caregiver–child interaction patterns, and gendered socialization—also shape linguistic experiences; girls often receive more verbally stimulating environments and are encouraged toward emotional expression, while boys face different interactional expectations. In conclusion, gender differences arise from a blend of biological, cognitive, and environmental dynamics. The findings have implications for educators, parents, and policymakers to design inclusive language-learning environments. Further research is recommended using longitudinal and cross-cultural approaches.